The algorithnt software program for cakulating the mechanical parameters of multilayer rod - Kleiza, Vytautas; Laurikietytė, Rita (Lietuvos matematikos rinkinys, 2004)
This work presents the software program for multilayer structural elements design. The main users of the software should be bachelor and master students of mechanical technology department and their professors as well. The program can be successfully applied for computations of mechanical characteristics of the real (industrial) problems. This program is able to choose the multilayer structural elements type and its mechanical and geometrical parameters. While the program is running the user can watch the calculated values of the parameters, plots of the main dependencies and explanations of main operations being performed with the program variables. The algorithm of the program assumes that the model multilayer structural elements is idealized, i.e. uniaxial stretching, which is simple and quite adequate. The program is developed for training purposes, so the algorithm used is idealized and not sophisticated but preserving the main features of multilayer structural elements calculation.